B Vitamins and Their Role in Immune Regulation and Cancer - Peterson, Christine Tara (Nutrients, 2020)
B group vitamins represent essential micronutrients for myriad metabolic and regulatory processes required for human health, serving as cofactors used by hundreds of enzymes that carry out essential functions such as energy metabolism, DNA and protein synthesis and other critical functions. B vitamins and their corresponding vitamers are universally essential for all cellular life forms, from bacteria to humans. Humans are unable to synthesize most B vitamins and are therefore dependent on their diet for these essential micronutrients. More recently, another source of B vitamins has been identified which is derived from portions of the 10(13) bacterial cells inhabiting the gastrointestinal tract. Here we review the expanding literature examining the relationship between B vitamins and the immune system and diverse cancers. Evidence of B vitamin’s role in immune cell regulation has accumulated in recent years and may help to clarify the disparate findings of numerous studies attempting to link B vitamins to cancer development. Much work remains to be carried out to fully clarify these relationships as the complexity of B vitamins’ essential functions complicates an unequivocal assessment of their beneficial or detrimental effects in inflammation and cancers.